2014
DOI: 10.1177/0886109913519789
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Gender Differences in Social Capital on Microenterprise Business Start-Up

Abstract: The Microenterprise Development Programs (MDPs) in the United States provide low-income women with business training and loans for their business start-up. This study investigates whether gender differences in social capital influence business start-up in order to find implications to improve female micro-entrepreneurs' business start-up. By analyzing the data from Panel Study of Entrepreneurial Dynamic (2001)(2002)(2003)(2004), this research finds that women are less likely to utilize bridging and linking soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 39 publications
5
46
0
6
Order By: Relevance
“…Of the 21 sources for advice (both public and private), women use ten sources to a greater extent than men; men use one source more than women; and women and men use ten sources equally. Our study supports Kim and Sherraden's (2014) study in which they claim women tend to have less access to networks (weak ties). A possible conclusion is that women use outside support to reduce their risks at start-up and to access information thorough network connections, Consistent with findings by Kim and Sherraden (2014), we also found that women use different business advisory services than men.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Of the 21 sources for advice (both public and private), women use ten sources to a greater extent than men; men use one source more than women; and women and men use ten sources equally. Our study supports Kim and Sherraden's (2014) study in which they claim women tend to have less access to networks (weak ties). A possible conclusion is that women use outside support to reduce their risks at start-up and to access information thorough network connections, Consistent with findings by Kim and Sherraden (2014), we also found that women use different business advisory services than men.…”
Section: Discussionsupporting
confidence: 90%
“…Our study supports Kim and Sherraden's (2014) study in which they claim women tend to have less access to networks (weak ties). A possible conclusion is that women use outside support to reduce their risks at start-up and to access information thorough network connections, Consistent with findings by Kim and Sherraden (2014), we also found that women use different business advisory services than men. For instance, women use advice from Family and relatives, Tax Office, Labour Office, Start-up courses, ALMI (National support for companies at all stages), Enterprise Agencies, Office for business support offered by the Municipality, Start-up guides on Internet, and an industry organisation.…”
Section: Discussionsupporting
confidence: 90%
“…Social networks consist of informal networks (family, relatives, friends, acquaintances) and formal business networks such as customers, distributors, suppliers, competitors, government (Gunto & Alias, 2014). Women entrepreneurs with high growth resources tend to use more formal social networks (Kickul et al, 2007) and those with low growth resources tend to use informal social networks (Kim & Sherraden, 2014).…”
Section: Social Network and Women Micro-enterprise Performancementioning
confidence: 99%
“…This is often noticed in job creation, and community development (Kim & Sherraden, 2014). For example, in Louisiana, 51% of privately owned firms were women which generated over $13 billion in sales and employed nearly 102,000 people in 2006 (Mahajar & Yunus, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation